2008
DOI: 10.1021/ja801478n
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Efficient 5-Endo-dig Cyclization of a Carbon-Centered Radical: 40 Years from a Prediction to Another Success for the Baldwin Rules

Abstract: Despite being predicted to be stereoelectronically favorable by the Baldwin rules, efficient formation of a C-C bond through a 5-endo-dig radical cyclization remained unknown for more than 40 years. This work reports a remarkable increase in the efficiency of this process upon beta-Ts substitution, which led to the development of an expedient approach to densely functionalized cyclic 1,3-dienes. Good qualitative agreement between the increased efficiency and stereoselectivity for the 5-endo-dig cyclization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 123 publications
1
43
0
Order By: Relevance
“…Now, the calculated cyclization barriers for the both competing cyclization of pyrazolyl reactants are in the order of 20 kcal/mol and both cyclizations are moderately endergonic. Similar effects of strain on the exo / endo selectivity have been reported for 4‐ exo /5‐ endo and 5‐ exo /6‐ endo radical cyclizations of alkynes. However, the exo ‐preference is even more pronounced for anionic cyclizations, so this switch in selectivity is more impressive.…”
Section: Description Of Computational Approachsupporting
confidence: 78%
“…Now, the calculated cyclization barriers for the both competing cyclization of pyrazolyl reactants are in the order of 20 kcal/mol and both cyclizations are moderately endergonic. Similar effects of strain on the exo / endo selectivity have been reported for 4‐ exo /5‐ endo and 5‐ exo /6‐ endo radical cyclizations of alkynes. However, the exo ‐preference is even more pronounced for anionic cyclizations, so this switch in selectivity is more impressive.…”
Section: Description Of Computational Approachsupporting
confidence: 78%
“…Surprised by the scarcity of radical 5‐endo‐dig cyclizations, we analyzed a variety of 4‐exo‐dig/5‐endo‐dig pairs computationally and found that the 4‐exo‐dig cyclization, unfavorable according to the rules and significantly less exothermic, is often faster than the alternative 5‐endo‐dig closure . Subsequent experimental work confirmed these predictions; only in the presence of an intramolecular interaction selectively stabilizing the 5‐endo TS could we obtain good yields of the 5‐endo products (Scheme ) ,…”
Section: Experimental Evidence: Exo‐digonal Closures Of Small Cyclesmentioning
confidence: 91%
“…Loss of SO2 can be a more selective process that loss of CO2. Due to applications of RSO2 radicals in synthesis, 52 the search for new approaches to their generations continues. 53 In this context, the reverse process, i.e.…”
Section: Conclusion and Practical Implicationsmentioning
confidence: 99%